The Effect of Word Attack Strategy on Student’s Reading Comprehension - Artha, Dewi Juni; Sari, Ambar Wulan; Nurhalimah, Siti (English Teaching and Linguistics Journal (ETLiJ), 2024)
This research aimed to provide empirical evidence of the impact of the Word Attack Strategy on students' achievement in reading descriptive texts, specifically among seventh-grade students at SMP Negeri I Teluk Mengkudu. The study was conducted as experimental research, with the population consisting of all seventh-grade students. The sample included 20 students in the experimental group and 19 students in the control group. Data was collected using a test as the primary instrument and analyzed using a t-test formula. The analysis revealed that the mean score of the experimental group was 94.25, while the control group had a mean score of 71.05. The findings indicate that the Word Attack Strategy had a significant effect on reading skills, as evidenced by the t-score (t₀) of 6.189, which was higher than the t-table (tₜ) value of 1.687 at a significance level of 0.05. Therefore, the hypothesis (Ha) is accepted, demonstrating that the Word Attack Strategy is more effective and significant in improving reading skills compared to conventional methods.